UJI BAKTERIOLOGIS SUSU KEDELAI PRODUK RUMAH TANGGA YANG DI JUAL DIPASARAN - Helpida, Helpida; Indriati, Gustina; Irdawati, Irdawati (Pendidikan Biologi, 2013)
ABSTRACKSoy milk is a food that has ingredients such as soy. Soy milk has a complete nutrient such as protein, carbohydrates, fats, minerals and vitamins. Complete nutrient content and high nutritional value, in convenient contaminated milk caused by microorganisms such as E. coli and Coliform. Associated with that we conducted this study aimed to determine the water quality of the bacteriological soy milk. This study was conducted from July to September 2013 is housed in the Laboratory of Microbiology Department of Biology, State University of Padang. This research is a descriptive study with random sampling. This study uses the Most Probable Number (MPN) using a two-stage trial testing the prediction (Presumtive Test) and test of certainty (Confirmative Test) with a range of 5:1:1. The results showed that soy milk is only 40% that meet the standards and 60% did not meet the standards set by the Ministry of Health No. 416/MENKES/PER/IX/1990 of the Terms and Drinking Water Quality Monitoring.